A fused thieno[3, 2-b]thiophene-dithiophene based donor molecule for organic photovoltaics: a structural comparative study with indacenodithiophene. Issue 41 (30th September 2016) - Abe, Yuichiro; Li, Hairong; Yin, Jun; Soci, Cesare; Grimsdale, Andrew C.; Lam, Yeng Ming
Abstract : A fused thieno[3, 2- b ]thiophene-dithiophene-based small molecular donor was synthesized and its properties were systematically compared with the corresponding indacenodithiophene-based molecule. Abstract : A novel donor material, di(HTh2BT)DTCTT, having a dithienocyclopenta-thieno[3, 2- b ]thiophene (DTCTT) core, was synthesized and used as the molecular donor in a small molecular organic photovoltaic device (sm-OPV). DTCTT has a molecular structure similar to that of indacenodithiophene (IDT) but with a central thienothiophene instead of a benzene, and the effect of the more extended conjugation of the theinothiophene on its optical, thermal and photovoltaic properties was systematically investigated. Di(HTh2BT)DTCTT showed red-shifted absorption (up to 800 nm), a higher HOMO level and greater crystallinity than its IDT analogue. The DTCTT based sm-OPV devices were fabricated by spin-coating a blend solution with PC71 BM, and showed an encouraging PCE of 2.8% with J sc of −9.3 mA cm −2, V oc of 0.73 V and FF of 0.42. This is the first report of a DTCTT-based molecular donor for sm-OPV and it can be seen that this compound has greater potential for achieving high efficiencies compared with its IDT analogue. The structural and morphological analyses indicated that further improvement may be possible by increasing the crystallinity of the blend film.